Implementation of Pharmacy-Based Vaccination against Human Papillomavirus: A scoping review of literature - Rapajić Moran, Ivana; Odalović, Marina (Archives of Pharmacy, 2025)
In most EU countries, pharmacists as community-based health care professionals (HCPs) can provide education and vaccination services, which can enhance convenience and accessibility for patients. This is especially important in areas where vaccine-coverage rates (VCRs) are suboptimal and in underserved areas where access to healthcare practitioners (HCPs) may be limited. The aim of this review is to describe the impact and feasibility of Human Papillomavirus (HPV) - related pharmacy-based vaccination (PBV) programs. The findings indicate that expanding access to vaccinations through pharmacies has the potential to improve immunization rates, particularly in underserved or hard-to-reach populations. Pharmacists’ roles as advocates, educators, and vaccine providers can address barriers, improve awareness, and promote vaccination uptake. Collaboration with other HCPs is essential enabling a comprehensive approach to HPV vaccination promotion.In conclusion, PBV programs have the potential to serve as an effective strategy for improving immunization rates in both rural and urban areas. The integration of pharmacies, through multi-disciplinary approach into HPV immunization programs can expand access, spread awareness, provide education, clarify concerns, increase convenience, and reach underserved populations. However, careful planning, training, and collaboration with other HCPs such as physicians and nurses, are necessary to overcome challenges and ensure the safe and efficient delivery of vaccines through pharmacies.
Keywords: pharmacy; HPV; vaccination; public health; urban; rural